THE IMPLICATIONS OF THE CONVERSATION IN THE TRAILER OF THE ACEH COMEDY FILM - Azhari; Widia Tamara; Rifki (RADJA PUBLIKA, 2023)
This study aims to describe the implications of general conversation, the implications of scaled conversations, and the implications of specific conversations in Acehnese comedy films. The research method used in this study is a qualitative research method. The data collection techniques used are documentation techniques and listening techniques. The data analysis technique of this research is by transcribing the entire content of the film, marking the implications, interpreting, and making conclusions. The test of the validity of the data in this study is by checking and fading experts. Based on the results of the study, the dominant implications used in Acehnese comedy films are the special conversation implications of eighty-one speeches, then the general conversation implications of thirty-four speeches, and the five-speech scale conversational implications. The implication of special conversation in the form of the use of the speaker's language tends to use special words that only the speaker can understand the meaning or intent of the speech. This Acehnese comedy film is personal and familial in delivering speeches by speakers who are packed with humor.